The vascular endothelial growth factor-A gene polymorphism predicts clinical outcomes among acute ST-segment elevation myocardial infarction patient - Kutia, I. M.; Kopytsya, M. P.; Hilova, Y. V.; Petyunina, O. V.; Berezin, A. E.; Кутя, І. М.; Копиця, М. П.; Хілова, Ю. В.; Петюніна, О. В.; Березін, Олександр Євгенійович (My University, 2020)
Context: Vascular endothelial growth factor (VEGF) is an angiopoetic factor, the variability of circulating level of which is mediated by expression of specific VEGF-A gene variants. Aims: To investigate the predictive role of VEGF-A gene polymorphism for clinical outcomes in ST-segment elevation myocardial infarction (STEMI) patients. Settings and Design: An open prospective singlecenter cohort study. Methods and Material: 135 patients with acute STEMI and 30 healthy volunteers were enrolled in the study. The G634C polymorphism in the VEGF-A gene was performed by real-time polymerase chain reaction at baseline. The 6-month combined clinical endpoint was determined. Statistical analysis used: The univariate and multiple variate logregression analysis. Results: The entire patient population was distributed into two groups depending on G634G-genotype (n = 70) and combination with G634C and C634C-genotypes (n=65). Unadjusted multivariate regressive logistic analysis has shown peak troponin I at admission, Killip class of heart failure > 2, GC/CC polymorphisms in VEGF-A gene, dynamic increased NT-proBNP and VEGF-A levels for 6 months, and remained independent predictors for the combined endpoint. After adjustment for dynamic changes of NT-proBNP and VEGF-A levels, the GC/CC polymorphisms in the VEGF-A gene remained an independent predictor of clinical outcome. Kaplan-Meier curves have demonstrated that GG VEGF-A genotype was associated with a lower frequency of combined endpoint when compared with GC/CC VEGF-A genotypes (Log-rank p = 0.02). Conclusions: The G634C polymorphism in the VEGF-A gene was found as an independent predictor for 6-month combined endpoints amid STEMI patients.
Keywords: ST-segment elevation myocardial infarction; single nucleotide polymorphism G634C; vascular endothelial growth factor; prediction; outcomes